Probiotic Potential of Lactobacillus Strains Isolated From Fermented Vegetables in Shaanxi, China - Liu, Chen; Xue, Wen-jiao; Ding, Hao; An, Chao; Ma, Sai-jian; Liu, Yao (Frontiers in Microbiology, 2022)
The objective of this study was to assess in vitro probiotic potential of Lactobacillus strains derived from handmade fermented vegetables in Shaanxi province, China. A total of 74 strains, Gram-positive, acid-producing and rod-shaped under the microscope, were isolated from 16 samples of spontaneously fermented vegetables in Shaanxi. Twenty-seven strains showed high survival under low pH and high bile salts conditions and were subjected to identification based on 16S rDNA gene sequence analysis. The results showed that 16 isolates belonged to Lactiplantibacillus plantarum (formerly known as Lactobacillus plantarum), 9 isolates belonged to Levilactobacillus brevis (formerly known as Lactobacillus brevis) and the remaining 2 strains belonged to Weissella viridescens. The 25 Lactobacillus strains were investigated for their survival rate to transit simulated gastrointestinal tract, cell surface hydrophobicity, auto-aggregation, co-aggregation with pathogen, adhesion to Caco-2, antimicrobial activity, antibiotics susceptibility, radical scavenging ability, α-glucosidase inhibition and the cholesterol assimilation. The results showed that the probiotic characteristics were strain-dependent and several strains exhibited excellent potential with specific probiotic properties, which indicated that they might be excellent candidates for production of functional foods to promote health benefits. Interestingly, it was firstly found that L. plantarum generally had higher antibacterial activities, α-glucosidase inhibition, and antibiotics susceptibility compared to L. brevis in this study. On a whole, results obtained in this study indicated that the Lactobacillus strains from handmade fermented vegetables from Shaanxi province, China, could be exploited as a source of novel probiotic LAB strains.